Republic of Serbia : Fifth Review under the Policy Coordination Instrument-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2021)
Recent economic developments. Economic activity recovered following a severe contraction in 2Q2020 caused by the pandemic. Real output in 2020 has been revised up and is now projected to contract by only 1.5 percent, on the back of positive highfrequency indicators. Inflation remains low. The banking system remains liquid. After the two waves in March and July, the number of new infections has accelerated again since mid-October, reaching record-high levels and a larger-than-expected deterioration presents a clear downside risk.